Optimizing of the take off in ski jumping - Müller, S.; Mahnke, R.; Schleichardt, A. (Science and Skiing V. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2012)
INTRODUCTION: In ski jumping the take-oft is a key position within the entire movement. The execution of take-off, the jump intensity (vertical take-off velocity) and the angular momentum generated with the take-off have a direct impact on the take-in of the flight posture (Hildebrand, Drenk & Müller, 2008). Analyses of international best practise show a variety of different sport technical solutions regarding the varying deployment of the upper body. The execution of the take-off movement is an optimization process because it is impossible to maximize the vertical take-off velocity and minimize the air resistance simultaneously. Using computer simulations it was intended to simulate different motion sequences and to generate knowledge on optimal execution of take-off.